Minimizing Makespan In Flow Shop Scheduling: The CDS Method with Overlapping - Yuniar, Sri Suci; Kusvianto, Arintyo Adi; Afifah, Alif Ulfa (Fakultas Sains dan Teknologi Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
This study implements the Campbell, Dudek, and Smith (CDS) scheduling method with overlapping to enhance production efficiency, with the primary objective of minimising makespan through strategic job overlapping. The overlapping technique divides the selected job into two batches, where the first batch, upon completing Machine 1, immediately proceeds to Machine 2, while the second batch undergoes Machine 1. Once the second batch completes Machine 1, it is transferred to Machine 2. Machine setup is only performed upon job arrival. The results indicate a lead time saving of 83 minutes, reflecting a significant reduction in total processing time. These data suggest the efficiency of the CDS method’s overlapping approach in optimising scheduling performance and resource utilisation. Keywords: Scheduling, CDS, multi-machine flow shop, Overlapping